Anti-nuclear matrix protein 2 antibody-associated juvenile dermatomyositis with gastrointestinal perforations was successfully treated with traditional therapeutic drugs combined with vedolizumab: a case report after a long-term follow-up and a review of the literature - Xu, Xue-mei; Ye, Shuang; Jin, Ying-ying; Liu, Chen-xi; Bao, Sheng-fang; Huang, Hua; Ding, Fei; Yang, Zhen; Jin, Yan-liang (Frontiers in Pediatrics, 2025)
Gastrointestinal perforation in patients with juvenile dermatomyositis has been reported as a life-threatening complication in the literature. However, effective treatment of juvenile dermatomyositis with gastrointestinal perforation remains challenging. We report the case of a patient who developed intestinal perforation 5 months after being diagnosed with anti-nuclear matrix protein 2 antibody-positive juvenile dermatomyositis. We systematically reviewed the literature on the medical and/or surgical treatment of gastrointestinal perforation in juvenile dermatomyositis. In addition to our case, as of October 2023, we identified 29 cases of gastrointestinal perforation in patients with juvenile dermatomyositis. Current treatment options for gastrointestinal perforation in juvenile dermatomyositis mainly include corticosteroids, methylprednisolone pulses, rituximab, intravenous immunoglobulin, cyclophosphamide, methotrexate, cyclosporine A, mycophenolate mofetil, and other traditional disease-modifying anti-rheumatic drugs. Notably, juvenile dermatomyositis complicated by gastrointestinal perforation is always associated with disease severity and activity. However, these are extremely severe patients who may not respond to treatment with methylprednisolone pulses and rituximab. Given the limited efficacy of conventional high-intensity systemic immunosuppressive therapy for juvenile dermatomyositis with gastrointestinal perforation, there is an urgent need to explore novel therapeutic approaches. We report on the successful use of vedolizumab in combination with corticosteroids, cyclophosphamide, and intravenous immunoglobulin as a novel therapeutic strategy for treating juvenile dermatomyositis complicated by gastrointestinal perforation. Importantly, up to now, there has been no report of juvenile dermatomyositis with gastrointestinal perforation treated with vedolizumab combined with traditional disease-modifying anti-rheumatic drugs in children.